Age-Specific Mortality During the 2020 COVID-19 Pandemic and Life Expectancy Changes in the United States and Peer Countries, 1980–2020. (22nd February 2022) - Masters, Ryan K; Woolf, Steven H; Aron, Laudan Y
Abstract: Objectives: Since the 1980s, life expectancy at birth ( e 0 ) in the United States has fallen steadily behind that of other high-income countries, widening the U.S. e 0 disadvantage. We estimate how that disadvantage was affected by high mortality rates in 2020, the first full year of the coronavirus disease 2019 pandemic. Methods: We contrast male and female e 0 in the United States and 18 peer countries for years 1980, 1995, 2010, 2019, and 2020. Using Arriaga decomposition, we show how differences in age-specific death rates have contributed to U.S. e 0 disadvantages. Results: In 2020, U.S. male and female e 0 changed by −2.33 (−2.50, −2.15) and −1.69 (−1.85, −1.53) years, respectively, whereas corresponding changes in peer countries averaged −0.67 (−0.82, −0.51) and −0.50 (−0.65, −0.35) years, respectively. This accelerated a longstanding and widening U.S. e 0 disadvantage relative to its peers, which increased from 3.49 to 5.15 years in males and from 2.78 to 3.97 years in females between 2019 and 2020. Whereas deaths before age 65 accounted for 55% and 40% of declines in U.S. male and female life expectancy, respectively, they accounted for only 24% and 11% of the respective declines in peer countries. Discussion: U.S. life expectancy declines in 2020 were larger than in peer countries and involved deaths across a broader age range, particularly among young and middle-aged adults. Both the longstanding U.S. e 0 disadvantage and acute losses of life in 2020 signal the need for systemic policy changes in the United States.